2021
DOI: 10.3390/ma14216357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Deep Cryogenic Treatment on AISI 52100 and AISI D3 Steel’s Corrosion Resistance

Abstract: The effect of deep cryogenic treatment (DCT) on corrosion resistance of steels AISI 52100 and AISI D3 is investigated and compared with conventional heat-treated counterparts. DCT’s influence on microstructural changes is subsequently correlated to the corrosion resistance. DCT is confirmed to reduce the formation of corrosion products on steels’ surface, retard the corrosion products development and propagation. DCT reduces surface cracking, which is considered to be related to modified residual stress state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…[14] reported worsened corrosion behaviour of cryogenically treated AISI D3 steel in 3.5% NaCl solution. However, also opposite result, > 50% improvement in corrosion resistance of AISI D3 steel in borate buffer with pH 10, was reported [15].…”
Section: Introductionmentioning
confidence: 93%
“…[14] reported worsened corrosion behaviour of cryogenically treated AISI D3 steel in 3.5% NaCl solution. However, also opposite result, > 50% improvement in corrosion resistance of AISI D3 steel in borate buffer with pH 10, was reported [15].…”
Section: Introductionmentioning
confidence: 93%
“…Patricia et al used scanning electron microscopy to study the corrosion resistance of AISI 52100 and AISI D3 steel after deep cold treatment and conventional heat treatment. They found that deep cold treatment reduced surface cracking by reducing residual stress [9] . Kara et al investigated the effect of cryogenic treatment on the wear performance of Sleipner tool steel.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that deep cryogenic treatment (DCT) can significantly increase the properties of alloy steels [8][9][10][11]; thus, it is used as a final treatment for many technologies and industries, such as materials science [12,13], tool and steel industries [14][15][16][17][18], manufacturing of rolls [19], and automotive industry [20]. This process uses sub-zero temperature, below −125 • C, which is created by liquid nitrogen [18], as the preferred cooling medium.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to low diffusion rate, significant changes are not expected at such low temperatures [48]. On the other hand, most researchers use significant DCT exposure times (24 h or more) to obtain significant changes in the structure and distribution of carbides [8,10,13,18,33,40,51].…”
Section: Introductionmentioning
confidence: 99%